Comparison of efficacy and complications between radiofrequency ablation and repeat surgery in the treatment of locally recurrent thyroid cancers: a single-center propensity score matching study. (1st January 2019) - Choi, Yangsean; Jung, So Lyung; Bae, Ja-Sung; Lee, So-Hee; Jung, Chan-Kwon; Jang, Jinhee; Shin, Na-Young; Choi, Hyun Seok; Ahn, Kook-Jin; Kim, Bum-Soo
Abstract: Purpose: To compare the efficacy and complication rates of radiofrequency ablation (RFA) and repeat surgery in the treatment of locally recurrent thyroid cancers. Materials and methods: A total of 221 patients with locally recurrent thyroid cancers who underwent either RFA ( n = 96) or repeat surgery ( n = 125) between March 2008 and March 2017 were retrospectively enrolled (range of follow-up, 1–10 years). Each cohort consisted of 70 patients after propensity score adjustment. Patients with more than three recurrent lesions were excluded. The primary and secondary end points were recurrence-free survival and complication rates, respectively. Recurrence-free survival curves were compared via the log-rank test. The complications—voice changes, hypocalcemia, and immediate procedural complications—were compared between the groups. In addition, pretreatment serum thyroglobulin ( T g ) levels and those at the last follow-up were also compared between the two groups to examine therapeutic efficacy. Results: After propensity score matching, both groups showed no significant differences in baseline characteristics. The recurrence-free survival rates were comparable between the RFA and surgery groups ( p = .2). There were no significant differences in mean serum T g levels and their mean decrease after treatment between the groups ( p = .891 and p = .963, respectively). Immediate procedural complications and voice changes also showed no significant between-group differences ( p = .316, p = .084, respectively). Hypocalcemia occurred only in the repeat surgery group ( n = 18). Overall complications were significantly more frequent in the repeat surgery group (RFA, n = 7; surgery, n = 27; p < .001). Conclusion: RFA may be an effective and safe alternative to repeat surgery in the treatment of a small number of locally recurrent thyroid cancers.